Knoweldge, Attitude and Practices of Women Towards Screening for Cervical Cancer - Muneeza Abdul Haleem, Salma Khalid, Uzma Zia, Rana Abid Ali, Sameen Fatima, Aneeza Sikander (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cervical cancer poses a major health challenge, especially in low- and middle-income countries (LMICs) such as Pakistan, where public awareness, routine screening, and preventive measures remain insufficient. Objective: The objective of the study is to evaluate the knowledge, attitudes, and practices (KAP) related to cervical cancer screening. Methods: A descriptive cross-sectional study was carried out at Central Park Teaching Hospital, Lahore, from March to September 2022. A total of 371 women participated. Data was gathered through structured proforma and assessed using SPSS version 25. Results: Only 34.8% of the participants were aware of cervical cancer screening methods, and merely 14.8% had ever undergone screening. Despite this, 74.1% considered screening important. Awareness and participation in screening were significantly higher among women with greater educational attainment, professional employment, and better socioeconomic status (p<0.001). Nevertheless, actual screening uptake remained low even within more educated groups. Conclusion: The study identifies a significant disconnect between knowledge, attitudes, and real-world practices. These findings emphasize the urgency of designing targeted, culturally appropriate strategies that enhance awareness and ensure accessible, affordable screening services, especially for underserved and less educated populations. Keywords: KAP study, women’s health, socioeconomic disparities, cervical cancer